The revenue effect of a global effective minimum tax - Clemens Fuest; Florian Neumeier (EconPol Forum, 2022)
We estimate the fiscal effect of a global effective minimum tax for Germany, the EU27, and the world. Our results indicate that Germany and - on aggregate - the EU27 would benefit fiscally from a global effective minimum tax. However, the size of the additional tax revenue depends on the design of the carve-out rule and the extent of behavioral adjustments on the side of multinational companies and low-tax countries
Keywords: 330